European Association of Urology Guidelines on Upper Urinary Tract Urothelial Carcinoma: 2023 Update - Rouprêt, Morgan; Seisen, Thomas; Birtle, Alison J.; Capoun, Otakar; Compérat, Eva M.; Dominguez-Escrig, José L.; Gürses Andersson, Irene; Liedberg, Fredrik; Mariappan, Paramananthan; Hugh Mostafid, A.; Pradere, Benjamin; van Rhijn, Bas W.G.; et al. (European urology, 2023)
The European Association of Urology (EAU) guidelines panel on upper urinary tract urothelial carcinoma (UTUC) has updated the guidelines to aid clinicians in evidence-based management of UTUC. To provide an overview of the EAU guidelines on UTUC as an aid to clinicians. The recommendations provided in these guidelines are based on a review of the literature via a systematic search of the PubMed, Ovid, EMBASE, and Cochrane databases. Data were searched using the following keywords: urinary tract cancer, urothelial carcinomas, renal pelvis, ureter, bladder cancer, chemotherapy, ureteroscopy, nephroureterectomy, neoplasm, (neo)adjuvant treatment, instillation, recurrence, risk factors, metastatic, immunotherapy, and survival. The results were assessed by a panel of experts. Even though data are accruing, for many areas there is still insufficient high-level evidence to provide strong recommendations. Patient stratification on the basis of histology and clinical examination (including imaging) and assessment of patients at risk of Lynch syndrome will aid management. Kidney-sparing management should be offered as a primary treatment option to patients with low-risk UTUC and two functional kidneys. In particular, for patients with high-risk or metastatic UTUC, new treatment options have become available. In high-risk UTUC, platinum-based chemotherapy after radical nephroureterectomy, and adjuvant nivolumab for unfit or patients who decline chemotherapy, are options. For metastatic disease, gemcitabine/carboplatin chemotherapy is recommended as first-line treatment for cisplatin-ineligible patients. Patients with PD-1/PD-L1–positive tumours should be offered a checkpoint inhibitor (pembrolizumab or atezolizumab). These guidelines contain information on the management of individual patients according to the current best evidence. Urologists should take into account the specific clinical characteristics of each patient when determining the optimal treatment regimen according to the risk stratification of these tumours. Cancer of the upper urinary tract is rare, but because 60% of these tumours are invasive at diagnosis, timely and appropriate diagnosis is most important. A number of known risk factors exist.